Accounting measurement of intangible assets implementing VAIC tm model - Rastić Amer; Stevanović Tatjana; Staletović Maja (Trendovi u Poslovanju)
Facilitated and stimulated transfer of knowledge, primarily due to digital technology and globalization, enabled subjects in the economy to actively use it in order to achieve success in business. The company's portfolio becomes enriched with resources or assets whose main substantial element is knowledge. However, knowledge is not easy to track and include in business books. Due to the fact that it cannot be seen or touched, additional efforts have been made by researchers to develop a quality accounting methodology. In addition to the fact that in the context of accounting, knowledge is qualified as an intangible asset, the methodology of financial accounting has been improved, and various models of its measurement have been offered in the literature. In particular, the VAIC model for measuring the efficiency of using intangible assets stands out in the literature.